Characteristics of arterial catheter use and related complications in dogs and cats in an intensive care unit. Issue 4 (14th June 2021) - Hagley, Matthew J.; Hopper, Kate; Epstein, Steven E.
Abstract: Objective: To identify characteristics of arterial catheter use, including indwelling times and reasons for removal, and analyze potential risk factors for complications based on patient‐ and catheter‐related variables. Design: Prospective clinical study from July 2012 to September 2016. Setting: University teaching hospital. Animals: One hundred ninety‐eight dogs and 29 cats with an arterial catheter monitored in the ICU. Interventions: None. Measurements and Main Results: A questionnaire was used to obtain patient and catheter information for arterial catheters monitored in the ICU during the study period. Two hundred twenty‐seven catheters met the inclusion criteria. Most catheters were placed in the dorsal metatarsal artery in dogs (90.4%) and either the dorsal metatarsal artery (51.7%) or coccygeal artery (48.3%) in cats. Weights ranged from 1.5 to 64 kg in dogs and 0.77 to 8.7 kg in cats. The median indwelling time was 24 hours for dogs and 12 hours for cats. Minor complications occurred in 19.2% of catheters in dogs and 17.2% of those in cats with removal of catheter due to complications in 13 of 198 (6.6%) for dogs and 2 of 29 (6.9%) for cats. There was no association between the incidence of complications and patient weight, catheter indwelling time, species, insertion site, catheter size, or level of consciousness during placement. There was also no association between the method of catheter maintenance (intermittent flushing or continuous pressure transducer) and the failure of a catheter to aspirate or flush. Conclusions: Arterial catheter‐related complications were relatively frequent, but most complications were minor and did not justify removal of the catheter. This suggests that the use of arterial catheters in both species is relatively safe. However, further research is needed to assess complications related to longer catheter indwelling times, particularly in cats.